Crianças cegas e videntes na educação infantil : características da interação e proposta de intervenção - França, Maria Luiza Pontes de (2008)
A reduced number of empiric studies treats of the characterization of the social interactions between blind children and sighted children and of the effectiveness of the activities developed to stimulate those interactions in the atmosphere of the Childish Education, what hinders the proposition of strategies consequent and well happened of inclusion. Blind children that received constant and specialized stimulation or non-systematic stimulation have different possibilities of exploration of the atmosphere that share with the friends in the school and of interaction with your peers. Those possibilities can be strongly related to the possibility of independent and safe displacement in the space that they frequent proportioned by motor development. The objectives of this study were: 1) to characterize the social interaction of blind children that received or not constant and specialized stimulation; 2) to characterize the social interaction of blind and sighted children; 3) appraised the effect of intervention proceedings in inclusive school environment in the repertoire of social interactions blind child with sighted children and in their motor development. Two blind children and their classmates of inclusive classroom participated of this study. They are from different institutions, with ages until 5 years old. Were organized situations where children could play free, beyond activities semi-structured with the objective of to promote interaction between the children and the motor development of the blind child. The children performances were registered in videotapes during the play situations. The treatment of data adopted a system of classification of interactions among children that it allowed the comparative analysis of the established interactions for the blind children and sighted. For evaluation of intervention were identified the manifestations of the blind child's behaviors referring to the social interaction listed as specific objectives. To evaluate the possible advancement of the blind child's motor development were conducted evaluations before and after the activities semi-structured through the Inventário Portage Operacionalizado (IPO) and of manual and in video registrations. Found it significant differences when comparing the characteristics of the blind children's interactions with the one of the sighted children, as well as in the comparison of the two blind children's acting. In the present study was observed that having constant and specialized stimulation the blind children it presents behaviors similar to the one of a child sighted in the school. With the intervention procedures, motor acting and interactive behaviors were included in the blind child's repertoire, making possible your insert in the school environment.